Crossfit exercises and their impact on the development of some special physical abilities and functional variables and the achievement of running (400 m) free for people with disabilities category deaf women - Ibrahim, Waleed Jaleel; Ahmed, Emad Khathim; Kareem, Nasir Hameed; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The CrossFit style is a modern technique, as an integrated training system, or a challenge to the elements of fitness. The importance of the research lies in investing CrossFit exercises and their training characteristics to develop special physical abilities. The problem of the research is that most trainers are moving away from the use of a modern training method like CrossFit, which contributes to the development of special physical abilities that have positive results in the development of achievement. After statistical data processing, the researchers concluded that the CrossFit exercises positively influenced the development of physical abilities of the research sample. Based on the conclusions, the researchers recommend using the modern CrossFit method in the training of raising the physical abilities level in athletics for the disabled.